Novel antipsychotics and extrapyramidal side effects. Theory and reality - Horácek, J (Pharmacopsychiatry, 2000)
Novel antipsychotics are less likely to produce extra-pyramidal symptoms (EPS). The superior EPS profile of these drugs compared with that of low-potency classic antipsychotics does not seem to be associated with an antimuscarinergic effect. Several other mechanisms could account for this typical feature of novel antipsychotics, which combines a strong antipsychotic effect with low liability to produce EPS. The hypotheses are based on either the receptor affinity or the topic selectivity of the drugs, but these effects are closely interconnected and it is not possible to separate them. For clozapine treatment, its very low D occupancy could explain the absence of EPS, but this does not account for the low EPS with other novel antipsychotics. The direct topic selectivity for extrastriatal D2 receptors and different distribution of the drug in the brain is less probable. The most plausible hypotheses are based on the concept of indirect topic selectivity for extrastriatal D2 receptors, mediated by high affinity for extrastriatal D2 receptors (D3, D4), 5-HT2A antagonism, alpha1 antagonism or muscarinergic antagonism at the limbic level. The D1 and indirect GABAergic antagonisms may play a role in the prevention of tardive dyskinesia. This paper briefly outlines the hypotheses and observations and summarizes the current knowledge of the occurrence of and risk for extrapyramidal side effects with novel antipsychotics.
Keywords: nemoci bazálních ganglií; receptory dopaminové; klinické zkoušky jako téma; Receptors, Dopamine; Humans; Mental Disorders; Receptors, Serotonin; Clinical Trials as Topic; lidé; antipsychotika; Antipsychotic Agents; Receptors, Adrenergic, alpha; receptory serotoninové; Basal Ganglia Diseases; duševní poruchy; alfa-adrenergní receptory